2018
DOI: 10.28945/4082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teacher Gender on Girls’ Performance on Programming Tasks in Early Elementary School

Abstract: Aim/PurposeThe goal of this paper is to examine whether having female robotics teachers positively impacts girls' performance on programming and robotics tasks Background Women continue to be underrepresented in the technical STEM fields such as engineering and computer science. New programs and initiatives are needed to engage girls in STEM beginning in early childhood. The goal of this work is to explore the impact of teacher gender on young children's mastery of programming concepts after completing an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
2
15
0
2
Order By: Relevance
“…The KIBO Mastery Challenges (KMCs) were used to gain insight into students' understanding of the KIBO programming language. The KMCs, a second iteration of the Solve-Its, utilized widely in previous studies (e.g., Sullivan & Bers, 2018;Sullivan, Bers, & Mihm, 2017;Sullivan, Strawhacker, & Bers, 2017), were embedded in the CAL-KIBO curriculum at four different points (at the end of lessons 4, 6, 8 and 12). They assessed students' mastery of the KIBO programming language and programming concepts taught up to that point in the curriculum (See Appendix B for more details about how the KMCs aligned with the curriculum).…”
Section: Kibo Mastery Challenges (Kmc)mentioning
confidence: 99%
“…The KIBO Mastery Challenges (KMCs) were used to gain insight into students' understanding of the KIBO programming language. The KMCs, a second iteration of the Solve-Its, utilized widely in previous studies (e.g., Sullivan & Bers, 2018;Sullivan, Bers, & Mihm, 2017;Sullivan, Strawhacker, & Bers, 2017), were embedded in the CAL-KIBO curriculum at four different points (at the end of lessons 4, 6, 8 and 12). They assessed students' mastery of the KIBO programming language and programming concepts taught up to that point in the curriculum (See Appendix B for more details about how the KMCs aligned with the curriculum).…”
Section: Kibo Mastery Challenges (Kmc)mentioning
confidence: 99%
“…Other research on students majoring in engineering has shown that having female role models may lead to higher levels of perseverance (Amelink & Creamer, 2010). Even at the early childhood and early elementary school level, research by Sullivan and Bers (2018) demonstrates that when girls in grades K-2 had a female robotics instructor they did not exhibit gender differences with boys in performance on programming tasks. However, when they had a male instructor, boys in the study performed statistically significantly better than girls on advanced programming tasks (Sullivan & Bers, 2018).…”
Section: Underrepresentation Of Female Mentors and Studentsmentioning
confidence: 98%
“…Past research suggests that exposing young children to STEM curriculum early on may prevent them from acting on gender-based stereotypes about STEM careers when they get older (Metz, 2007;Steele, 1997) and may also limit the number of roadblocks they have pursuing these fields down the road (Madill et al, 2007;Markert, 1996). Robotics can be a hands-on way for female students to gain skills in building, coding, engineering, design, and more beginning in early elementary school (Sullivan & Bers, 2016;Sullivan & Bers, 2018). For example, research with the KIBO robot has shown that beginning in early elementary school, boys are already significantly more interested in engineering than girls, and that completing a hands-on KIBO robotics curriculum increased girls' interest in engineering so that this gender difference was eliminated (Sullivan, 2016;Sullivan & Bers, 2018).…”
Section: Gender Disparity In Technology and Engineeringmentioning
confidence: 99%
See 2 more Smart Citations